Scenario-based assessment of fecal pathogen sources affecting bathing water quality: novel treatment options to reduce norovirus and Campylobacter infection risks - Rytkönen, Annastiina; Meriläinen, Päivi; Valkama, Kristiina; Hokajärvi, Anna-Maria; Ruponen, Josefiina; Nummela, Jarkko; Mattila, Harri; Tulonen, Tiina; Kivistö, Rauni; Pitkänen, Tarja (Frontiers in Microbiology, 2024)
Wastewater discharge and runoff waters are significant sources of human and animal fecal microbes in surface waters. Human-derived fecal contamination of water is generally estimated to pose a greater risk to human health than animal fecal contamination, but animals may serve as reservoirs of zoonotic pathogens. In this study, quantitative microbial risk assessment (QMRA) tools were used to evaluate the hygienic impact of sewage effluents and runoff water from municipalities and animal farms on surface and bathing waters. The human-specific microbial source tracking (MST) marker HF183 was used to evaluate the dilution of fecal pathogens originating from the sewage effluent discharge to the downstream watershed. According to the dilution pattern of the MST marker HF183, microbes from wastewater were effectively diluted (2.3-3.7 log10) in the receiving waters. By using scenario-based modeling, the health risks posed by exposure on human-specific norovirus GII and zoonotic Campylobacter jejuni during the bathing events were evaluated. The risk for gastroenteritis was found to be elevated during wastewater contamination events, where especially norovirus GII infection risk increased (1-15 cases per day among 50 bathers) compared to the business as usual (BAU) situation (1 case per day). The noted C. jejuni infection risk was associated with animal farm contamination (1 case per day, versus 0.2-0.6 cases during BAU). As novel risk management options, the efficiency of UV-LED disinfection and wetland treatment as well as biochar filtration were tested on-site for the contamination sources. Tertiary treatment of wastewater with wetland treatment and UV-LED disinfection reduced efficiently the water-borne gastroenteritis risks associated with bathing. Based on the experiences from this study, a QMRA-based approach for health risk evaluations at bathing sites can be useful and is recommended for the bathing site risk assessments in the future. In case of low pathogen numbers at the exposure sites, the MST marker HF183 could be used as a pathogen dilution co-efficient for the watershed under evaluation. The full-scale implementation of novel tertiary treatment options at WWTPs as well as on-site runoff water treatment options should be considered for infection risk management at locations, where scenariobased QMRA implies elevated infection risks to occur.